Digital finance : big data, start-ups, and the future of financial services - Beaumont, Perry H., 1961- (Abingdon, Oxon ; New York : Routledge, 2020)
"The internet is dramatically transforming the way business is done, particularly for financial services. Digital Finance takes a thoughtful look at how the industry is evolving, and it explains how to integrate concepts of digital finance into existing traditional finance platforms. This book explores what successful companies are doing to maximize their opportunities in this context and offers suggestions on how to introduce digital finance into a firm's structure. Specific strategies for a digital future are presented, alongside numerous case studies that explore key attributes of success. In recognition of the rapidly evolving nature of finance today, Digital Finance is accompanied by a website maintained by the author (PerryBeaumont.com), as well as links to other content with insightful articles, analyses, and opinions. Whether a practitioner or student of finance, Digital Finance provides rich context for better understanding the landscape of finance today, and lays a foundation for processing and creating the financial innovations of tomorrow"--
Includes bibliographical references and index
BBS
Trim education
Keywords: Financial services industry -- Technological innovations; Financial institutions -- Data processing; Big data; Finance; Business & finance